Construction of Virtual Neuron and Consolidation of Sleep and Memory Process– A Molecular Docking and Biomathematical Approach - Bin Zhao; Jinming Cao; Kuiyun Huang; Xia Jiang; Jingfeng Tang (Journal of Model Based Research, 2019)
This methods paper combines molecular docking and biomathematical modeling to construct a virtual neuron framework for studying sleep‑related memory consolidation. It outlines model components and validation approach.
Keywords: Virtual Neuron